Unraveling key determinants of corn productivity: A correlation study of soil chemistry, biology, and climate in Sumedang, West Java, Indonesia (Asian Journal of Agriculture, 2025)
Abstract. Sule MIS, Fitriatin BN, Siswanto SY, Nurbaity A. 2025. Unraveling key determinants of corn productivity: A correlation study of soil chemistry, biology, and climate in Sumedang, West Java, Indonesia. Asian J Agric 9: 201-207. Corn productivity in areas with diverse agroecological conditions is influenced by several environmental factors such as soil chemistry, soil physics, soil biology, and climate conditions. The influence of these factors on corn productivity is significant and necessary to maintain or even increase corn plant productivity. This study aims to examine the conditions of soil chemistry, soil biology, and corn land climate and identify the correlation between environmental factors and corn yields, thereby determining the main factors of corn productivity in Sumedang, West Java, Indonesia. The study conducted using purposive sampling and an analytical approach at 18 observation locations, has practical implications for agricultural practices. By analysis was carried out by analyzing total phosphorus, cation exchange capacity, organic carbon, soil pH, phosphate-solubilizing bacteria, arbuscular mycorrhizal fungi, rainfall, temperature, and humidity; the study provides valuable insights for optimizing corn cultivation. The results of the correlation analysis show that each environmental factor has a different correlation strength with corn productivity. Soil chemistry factors have a weak-moderate correlation (0.26-0.43), soil biology is very weak (-0.36 to 0.02), and climate is weak-strong (-0.78 to 0.74). Environmental temperature conditions positively correlate (r = 0.74) to corn productivity. This is likely due to increased soil mineralization processes, germination, and faster plant development at optimal temperatures. Conversely, environmental humidity negatively correlates (r = -0.78) to corn productivity. This is likely because increased humidity can increase the risk of plant diseases (fungi), decrease photosynthesis efficiency, and limit soil aeration, thus affecting the health of corn plant roots. These findings underline the importance of maintaining the suitability of the corn cultivation environment amidst climate change, especially in tropical climates such as Indonesia.
Keywords: Agroecosystem, crop yield, microbial activity, soil fertility, sustainable agriculture